2011
DOI: 10.1104/pp.111.179069
|View full text |Cite
|
Sign up to set email alerts
|

Subfunctionalization of Cellulose Synthases in Seed Coat Epidermal Cells Mediates Secondary Radial Wall Synthesis and Mucilage Attachment      

Abstract: Arabidopsis (Arabidopsis thaliana) epidermal seed coat cells follow a complex developmental program where, following fertilization, cells of the ovule outer integument differentiate into a unique cell type. Two hallmarks of these cells are the production of a doughnut-shaped apoplastic pocket filled with pectinaceous mucilage and the columella, a thick secondary cell wall. Cellulose is thought to be a key component of both these secondary cell wall processes. Here, we investigated the role of cellulose synthas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

12
201
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 134 publications
(213 citation statements)
references
References 55 publications
12
201
0
Order By: Relevance
“…Small amounts of cellulose, arabinan, and galactan were also found in Arabidopsis seed mucilage (Willats et al, 2001a;Macquet et al, 2007a;Young et al, 2008). Recent studies showed that cellulose plays an adhesive role for the attachment of mucilage pectin to the seed coat epidermal cells (Harpaz-Saad et al, 2011;Mendu et al, 2011;Sullivan et al, 2011). Variations in both mucilage composition and structure have been observed in other plants (Anderson, 1933;Muralikrishna et al, 1987;Naran et al, 2008).…”
mentioning
confidence: 93%
“…Small amounts of cellulose, arabinan, and galactan were also found in Arabidopsis seed mucilage (Willats et al, 2001a;Macquet et al, 2007a;Young et al, 2008). Recent studies showed that cellulose plays an adhesive role for the attachment of mucilage pectin to the seed coat epidermal cells (Harpaz-Saad et al, 2011;Mendu et al, 2011;Sullivan et al, 2011). Variations in both mucilage composition and structure have been observed in other plants (Anderson, 1933;Muralikrishna et al, 1987;Naran et al, 2008).…”
mentioning
confidence: 93%
“…A simple hypothesis for the role of CESA5 in mucilage adherence is that it synthesizes cellulose, which interacts with the mucilage pectin to mediate adherence. Loss of CESA5 function results in a reduction of mucilage cellulose biosynthesis and a less adherent mucilage cell wall matrix (Mendu et al, 2011;Sullivan et al, 2011). The role of SOS5 in mucilage adherence is more difficult to explain.…”
mentioning
confidence: 99%
“…Between approximately 5 and 9 d approximate time of fertilization (DPA), seed coat epidermal cells synthesize mucilage and deposit it in the apoplast, creating a donut-shaped mucilage pocket that surrounds a central cytoplasmic column (Western et al, 2000(Western et al, , 2004Haughn and Chaudhury, 2005). From 9 to 13 DPA, the cytoplasmic column is gradually replaced by a cellulose-rich, volcano-shaped secondary cell wall called the columella (Beeckman et al, 2000;Western et al, 2000;Windsor et al, 2000;Stork et al, 2010;Mendu et al, 2011).…”
mentioning
confidence: 99%
See 2 more Smart Citations